Bilateral Internal Iliac Artery Embolization Results in an Unacceptably High Rate of Complications in Patients Requiring Pelvic/Acetabular Surgery. Issue 9 (September 2018) - Lindvall, Eric; Davis, Jason; Martirosian, Armen; Garcia, Gustavo; Husak, Lisa
Abstract : Objectives: To assess complication rates in patients undergoing open reduction internal fixation (ORIF) of pelvic/acetabular fractures with and without pelvic angiography embolization (PAE). Design: Retrospective case series. Setting: Level 1 Trauma Center. Patients/Participants: One hundred eleven patients with pelvic or acetabular fractures that required orthopaedic fixation. Intervention: Retrospective analysis of outcomes in patients who underwent ORIF of pelvic/acetabular fractures with and without PAE. Main Outcome Measurements: Comparison of surgical wound infections, necrosis, and/or fracture nonunions between the PAE group and a control group (no PAE). Results: Final study groups consisted of 50 patients in the PAE group and 61 patients in the control group. Ninety-six percent of patients underwent nonselective PAE. Significantly higher complications were noted in the PAE group than in the control group (20% compared with 4.9%; P = 0.020). In addition, posterior surgical approaches combined with internal iliac artery embolization represented the highest complication rate. Conclusions: Patients requiring PAE and pelvic/acetabular ORIF should undergo a multidisciplinary treatment approach with the trauma surgeon, interventional radiologist, and orthopaedic surgeon before PAE being performed to decrease complications and avoid nonselective bilateral internal iliac artery embolization. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.